Memórias rabiscadas nas crônicas de Viventes das Alagoas de Graciliano Ramos - Silva, Regina Nascimento (2013)
This work, entitled Memórias rabiscadas nas crônicas de Viventes das Alagoas, reflects the chronicle as a time and memory gender -a writing of the time. Chronicles written by Graciliano Ramos in the decades of 1920 and 1950, which were compiled and published in the posthumous book Viventes das Alagoas, in 1962, are analyzed under this perspective. It starts with the assumption that chronicles reconstruct memory. So, life and experience are the materials of the chronicle, which is constituted itself as testimony of a life, document of a time or a means to register the history in the text. Thus, in these chronicles, it is analyzed how individual and collective memory are intertwined, tying themselves to the memory of that period, in which contradictions and ambiguities, used to define the intellectual positions of that time, colored by the debates about modernization, politics, culture, nation, people, among others, are put together in this gender. The text is organized in three chapters. The first presents the author s biography and his way as a chronicler, showing the extension and the variety of this chronicle production, as well as the historical and personal circumstances in which Graciliano finds the journal and, consequently, the chronicle. The second focuses the author s performance, by means of the chronicles, as an intellectual collaborator to the Cultura Políticamagazine. The third chapter presents the chronicler s insertion in the debates about culture and society, through memories and reminiscences. It s concluded that it is placed a cultural and social history of the northeastern sertãoin the Viventes das Alagoaschronicles, printed from the reconstitution of history and experiences of life, including Graciliano s, as a living person in this space.